Profil Pelajar Berkebhinekaan Global Menurut Al-Qur'an Surah Al-Hujurat Ayat 13. - Izzan, Ahmad; Solihin, Muhamad Ramdan (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
The Merdeka Curriculum proposed by the government in 2020-2021 presents the Pancasila Student Profile program in an effort to strengthen the character of students. This profile has been regulated in the Minister of Education and Culture regulation no. 22 of 2020. One of the profiles initiated is related to the dimension of global diversity. Q.S. Al-Hujurat verse 13, which is closely related to the dimension of global diversity, invites all mankind to maintain unity and diversity, help each other, foster a sense of compassion, because all humans come from one descent. There is no difference between men and women. Everyone is required to create peace in society and respect each other. The aim of writing this research is, 1) to find out how the Pancasila Student Profile is defined, 2) to find out how the concept of the Pancasila Student Profile has global diversity according to the Al-Qur'an Surah Al-Hujurat verse 13, and 3) to find out how relevant the Student Profile is. Pancasila has global diversity according to the Al-Qur'an letter Al-Hujurat verse 13 in the Independent Curriculum. This research uses a literacy study method. The results of the research explain that the Pancasila Student Profile's global diversity dimension has been stated in Surah Al-Hujurat verse 13 and there is relevance of the values ​​of the Pancasila Student Profile in the Independent Curriculum to the perspective of the verses in the Al-Qur'an, so that it can strengthen the character of students. . Apart from that, religion and nationalism can go hand in hand and be in harmony without any special dichotomy, provided that the Koran is always at the forefront and at the top.  Keywords: Pancasila Student Profile Values, Global Diversity, Al-Hujurat Verse 13